RELATED PARTY TRANSACTIONS AND EARNINGS MANAGEMENT IN MANUFACTURING COMPANIES IN INDONESIA - Yuliati, Retno; Handayani, Erika; Christano, Shania Milla; Budhijono, Fognawati (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2021)
This study examines the effect of the number of related party transactions (RPT) on earnings management through accruals and real earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The effect of RPT is seen from the entire amount of RPT recorded in the company's financial statements divided by the company's total assets (RPTOTAL). This study uses secondary data from the S&P Capital IQ and company annual reports that the public can access on the IDX website. The sampling technique used purposive sampling. There were 732 observations from 164 manufacturing companies during the 2014-2018 period—data analysis using multiple regression with the fixed-effects model. The results showed that the amount of RPT has a significant positive effect on accrual earnings management. However, there is no effect of the RPT amount on real earnings management. RPT is a transaction carried out for expropriation of minority shareholders, and to cover RPT losses, management has an incentive to manipulate through earnings management. This study contributes to the effect of RPT on earnings management in manufacturing companies in Indonesia. This study is a valuable starting point for similar research in other developing countries.